2017
DOI: 10.1371/journal.pone.0172875
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neonatal mortality in rural Northern Ethiopia: A population based nested case control study

Abstract: IntroductionIn low income and middle income countries, neonatal mortality remains high despite the gradual reduction in under five mortality. Newborn death contributes for about 38% of all under five deaths. This study has identified the magnitude and independent predictors of neonatal mortality in rural Ethiopia.MethodsThis population based nested case control study was conducted in rural West Gojam zone, Northern Ethiopia, among a cohort of pregnant women who gave birth between March 2011 and Feb 2012. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 8 publications
5
27
2
Order By: Relevance
“…Neonates born from mothers who have a 2-4 history of birth have 5.4 times hazard of death as compared to those with first birth. In contrast to this, a study conducted in Rural northern Ethiopia revealed that mothers who gave birth 2-4 times have 85% lesser hazard of losing their newborn for a neonatal death [11]. Also, those Neonates born from mothers who have a history of more than 5 births had 12.1 times hazard of death.…”
Section: Discussionmentioning
confidence: 83%
“…Neonates born from mothers who have a 2-4 history of birth have 5.4 times hazard of death as compared to those with first birth. In contrast to this, a study conducted in Rural northern Ethiopia revealed that mothers who gave birth 2-4 times have 85% lesser hazard of losing their newborn for a neonatal death [11]. Also, those Neonates born from mothers who have a history of more than 5 births had 12.1 times hazard of death.…”
Section: Discussionmentioning
confidence: 83%
“…The incidence of neonatal mortality was lower than studies done in northern Ethiopia (18.6 per 1000 live births), Kersa Health and Demographic Surveillance system site in Ethiopia (27.5 per 1000 live births) and two studies in southwest Ethiopia (35.5 and 27 per 1000 live births). But, it was higher than one study done in South Central Ethiopia (4.8 per 1000 live births) [10,[12][13][14][15]. The reason for this is the study period difference along with advance in the health care system that people's attitudes and awareness about conditions that put the newborn for ill health and increase in healthseeking behavior from time to time.…”
Section: Discussionmentioning
confidence: 79%
“…Analysis of different studies in Ethiopia showed that the incidence of the neonatal mortality rate was ranged from 17.2 to 35.5 per 1000 live births [10][11][12][13][14][15]. The most determinate factors which were identified by previous studies were birth order, frequency of antenatal care, delivery place, twin delivery and size of neonate [10,16,17].…”
mentioning
confidence: 99%
“…In line with the Mosley and Chen conceptual framework [27], different confounders that have been conceptually linked to neonatal survival, such as women's age at birth [51,52], education level [30,31], working status [30], and alcohol consumption during index pregnancy [53] were also considered in this study. Moreover, obstetric and neonatal related variables such as utilization of antenatal and postnatal cares, number of previous pregnancies, parity, perceived weight of neonate at birth, place of birth and type of birth (singleton or multiple births) were considered as confounders in the association of IPVP and neonatal mortality [28,30,32,34].…”
Section: Control Variablesmentioning
confidence: 99%
“…Apart from IPV, socio-economic as well as obstetric and neonatal factors have been described by the Mosley and Chen conceptual framework on child survival [27]. Prior studies in Ethiopia documented risk factors such as young age at pregnancy or birth [28,29], living in rural area [29] and no or lower level of educational or employment status [30,31], which all relate to availability and use of limited resources in taking care of children that would indirectly contribute to the neonatal survival. Pregnancy and obstetric factors such as poor utilization of ANC, PNC or immunizations [28,32,33]; high gravidity and parity [28,30]; births occurring at home [32]; low birth weight [28,32,33] and multiple (as opposed to singleton) form of deliveries [28,33] have been extensively studied in the country.…”
Section: Introductionmentioning
confidence: 99%